The Activity of Liposomal Linolenic Acid Against Helicobacter pylori In Vitro and Its Impact on Human Fecal Bacteria - Wang, Ya; Wu, Shuang; Wang, Le; Wang, Youhua; Liu, Dongsheng; Fu, Yingjun; Xie, Yong (Frontiers in Cellular and Infection Microbiology, 2022)
Helicobacter pylori (H. pylori) infection is associated with a variety of gastrointestinal diseases. Here, we focused on the activity of a novel nanomedicine-liposomal linolenic acid (LipoLLA) against H. pylori and its impact on human fecal bacteria in vitro. The minimum inhibitory concentrations (MICs) of LipoLLA against 30 H. pylori clinical strains were determined in combination with amoxicillin (AMX), metronidazole (MTZ), levofloxacin (LVFX) and clarithromycin (CAM). Bactericidal activity was measured by generating concentration-bactericidal curves at different times and pH values. Leakage of glucose (GLU) and aspartate aminotransferase (AST) was detected, combined with detection of changes in morphology by electron microscopy, to study the mechanism of action of LipoLLA against H. pylori. The effect of LipoLLA on human fecal bacteria was studied by high-throughput sequencing of fecal samples. We observed a synergistic or additive effect when LipoLLA was combined with AMX, MTZ, LVFX and CAM. The concentration-sterilization curves were pH and time dependent. After treatment with LipoLLA, GLU and AST levels were increased (P<0.05), and the morphology of H. pylori changed significantly. Moreover, LipoLLA activity led to no significant changes in the intestinal flora in terms of alpha diversity, species composition, beta diversity, etc. In conclusion, LipoLLA showed good anti-H. pylori effects. It destroyed the outer membrane barrier and caused leakage of the bacterial contents to achieve anti-H. pylori effects. And LipoLLA had little effect on human fecal bacteria in vitro.